Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.jafc.9b05321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Potent Odorants in Raw and Ripened Pu-Erh Tea Infusions Based on Odor Activity Value Calculation and Multivariate Analysis: Understanding the Role of Pile Fermentation

Abstract: Infusions prepared from raw pu-erh tea (RAPT) and ripened pu-erh tea (RIPT) showed remarkable aroma differences. Predominant odorants in RAPT and RIPT infusions were identified and compared by the combined use of gas chromatography–olfactometry, aroma extract dilution analysis, odor activity values (OAVs), and multivariate analysis. A total of 35 and 19 odorants (OAV > 1) were detected in RIPT and RAPT, respectively. Odorants in RAPT and RIPT are significantly different in both odor properties and aroma compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 46 publications
1
68
0
Order By: Relevance
“…The roasted tea is generally formed, released and accumulated in the process of drying or enhancing aroma, which can improve the aroma quality of tea to a certain extent. [21] According to the analysis, in addition to the heterocyclic compounds that were furaneol and methyl-pyrazine, which were roasted, were positively correlated to roasted, the compounds with green or fresh, such as 1-hexanol, linalool, orcinol, ((Z)-2-penten-1-ol and (Z)-3-hexen-1-ol, were positively correlated with it. In the correlation analysis of sensory attributes of QDA (Table S2), it was also found that green and roasted, which were opposite to each other, appeared up in the same tea, and had a certain positive correlation.…”
Section: Correlation Analysis Of Volatile Components and Sensory Propmentioning
confidence: 94%
See 1 more Smart Citation
“…The roasted tea is generally formed, released and accumulated in the process of drying or enhancing aroma, which can improve the aroma quality of tea to a certain extent. [21] According to the analysis, in addition to the heterocyclic compounds that were furaneol and methyl-pyrazine, which were roasted, were positively correlated to roasted, the compounds with green or fresh, such as 1-hexanol, linalool, orcinol, ((Z)-2-penten-1-ol and (Z)-3-hexen-1-ol, were positively correlated with it. In the correlation analysis of sensory attributes of QDA (Table S2), it was also found that green and roasted, which were opposite to each other, appeared up in the same tea, and had a certain positive correlation.…”
Section: Correlation Analysis Of Volatile Components and Sensory Propmentioning
confidence: 94%
“…It is common in flavor characteristics for dark tea, and rarely found in black tea. [20,21] In the sample of this study, No. 3, No.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Recently, HPLC (Rahim et al., 2014; Zhang et al., 2013), LC‐MS (Zhao et al., 2019; Zhou et al., 2020), GC‐MS (Pang et al., 2019), electronic tongue (E‐tongue) (Hou et al., 2014), and electronic nose (E‐nose) (Yang et al., 2018) have been developed to determine nonvolatile and volatile components in tea, or carry out for the quality evaluation. Particularly, LC‐MS/MS metabolomics based on ultra‐high performance liquid chromatography‐quadrupole time of flight‐mass spectrometry (UHPLC‐Q‐TOF/MS) method coupled with multivariate statistical analyses, such as principal component analysis (PCA), orthogonal projection to latent structures discriminate analysis (OPLS‐DA), and hierarchical cluster analysis (HCA), have become a potent tool in distinguishing production place, storage environment and processing technologies of tea (Long et al., 2020; Ma et al, 2021; Wang et al., 2018; Zhou et al., 2019;).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, (E)-2-nonenal, frequently detected in various teas through GC-O, contributed slightly to both KBT aromas, with OAVs of 2 and 1 in the FKBT and 1Y-KBT infusions, respectively. Although dihydroactinidiolide was reported to be an aroma volatile in several teas [ 3 , 25 , 26 ], we did not perceive its aroma. However, the concentration of dihydroactinidiolide in the FKBT infusion was only 60% of that in the 1Y-KBT infusion according to standard addition, supporting our previous conclusion that dihydroactinidiolide was a reliable indicator of storage duration.…”
Section: Resultsmentioning
confidence: 57%